Lipid nanocapsules enhance the transdermal delivery of drugs regardless of their physico-chemical properties - Kalvodová, Aneta; Zbytovská, Jarmila (International journal of pharmaceutics, 2022)
The transdermal application of actives offers numerous advantages over other conventional routes. Namely, a stable level of drugs in the bloodstream and reduced side effects are the argument for topical administration. Unfortunately, the exceptional skin barrier and unsuitable physico-chemical properties of drugs are the limiting factors for the transdermal passage. It is possible to overcome this by incorporating the drug into nano-carriers to enhance its permeation through the skin barrier. For this purpose, we prepared lipid nanocapsules (LNCs) to modulate skin passage of three pharmaceutically important drugs - indomethacin (IND), diclofenac sodium (DF) and caffeine (CF). We present a stable system prepared by the phase inversion temperature method with particle size under 100 nm and PDI < 0.1 with great encapsulation efficiency for indomethacin and diclofenac. By FTIR it was possible to confirm (for IND and DF) or disprove (in case of CF) the incorporation of a drug into the LNCs. By ex vivo permeation experiments on porcine skin, we confirmed the superior effect of the LNCs on the APIs skin passage. The drug permeated through the skin with higher intensity when delivered from LNCs compared to other standard formulations. We show that lipid nanocapsules play an important role in enhanced topical application of actives.
Keywords: diklofenak; indomethacin; nosiče léků; lipidy; Nanocapsules; Drug Carriers; aplikace kožní; Indomethacin; velikost částic; Administration, Cutaneous; Diclofenac; Lipids; nanokapsle; Particle Size